Оценка рассчетных воздействий в параболических системах. $L_2$-подход - Bondarev, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
By using observations of solutions of the first initial boundary-value problem for a parabolic quasilinear equation with fast random oscillations, we estimate the nonlinear term of the equation. In the metric of the space $L_2$, we study large deviations of a nonparametric estimate of nonlinear influence.